The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1516-3180.2015.01850912
|View full text |Cite
|
Sign up to set email alerts
|

Are normal-weight adolescents satisfied with their weight?

Abstract: CONTEXT AND OBJECTIVE: The high prevalence of obesity has led to public policies for combating it. People with normal weight may gain greater awareness of this issue and change their perceptions of their weight. The aim of this study was to evaluate the prevalence of body weight dissatisfaction among normal-weight adolescents, according to demographic and socioeconomic variables, health-related behavior and morbidities. DESIGN AND SETTING: Population-based cross-sectional study that used data from a health sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 40 publications
0
12
0
12
Order By: Relevance
“…Moreover, attitudes toward thin body sizes and weight control can lead to poor dietary patterns in adolescents (Ganesan, Ravishankar, & Ramalingam, 2018). Body size dissatisfaction was associated with eating disorders (Martini, Assumpção, Barros, Canesqui, & Barros Filho, 2016) and with unhealthy weight control behaviors, regardless of nutritional status (Neumark‐Sztainer, Paxton, Hannan, Haines, & Story, 2006). Adolescents with body size dissatisfaction were more likely to present a restrictive eating pattern (Ribeiro‐Silva et al, 2018), and this relationship was stronger in those with overweight (Mitchell & Steele, 2016; Pedro et al, 2016), who were more likely to present abnormal frequencies and quantities of food consumption than normal weight adolescents (Caran, Santana, Monteiro, & da Veiga, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, attitudes toward thin body sizes and weight control can lead to poor dietary patterns in adolescents (Ganesan, Ravishankar, & Ramalingam, 2018). Body size dissatisfaction was associated with eating disorders (Martini, Assumpção, Barros, Canesqui, & Barros Filho, 2016) and with unhealthy weight control behaviors, regardless of nutritional status (Neumark‐Sztainer, Paxton, Hannan, Haines, & Story, 2006). Adolescents with body size dissatisfaction were more likely to present a restrictive eating pattern (Ribeiro‐Silva et al, 2018), and this relationship was stronger in those with overweight (Mitchell & Steele, 2016; Pedro et al, 2016), who were more likely to present abnormal frequencies and quantities of food consumption than normal weight adolescents (Caran, Santana, Monteiro, & da Veiga, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among the participants of the ERICA 2013-2014 (Study of Cardiovascular Risks in Adolescents), the prevalence of skipping breakfast went from 20.1% (95% CI: 18.8 to 21.6%) among adolescents aged 12 to 14 years to 24.0% (95% CI: 22.5 to 25.7%) among those aged 15 to 17 years 35 . In the Campinas Health Survey, the prevalence of dissatisfaction with one's weight was 43.7% (95% CI: 37.9 to 49.8%) among those in the ideal weight range, reaching a prevalence ratio of 1.4 (95% CI: 1.1 to 1.7) in the 15-to-19-year-old age group compared to the 10-to-14-year-old age group 36 .…”
Section: Discussionmentioning
confidence: 97%
“…Analyzing dissatisfaction with body image, Conti et al 24 found that adolescents of both sexes demonstrated concerns with weight, body size and appearance; the aspects that most caused dissatisfaction were weight, stomach and thighs among the boys and weight, chest/breasts and stomach among the girls. In a study conducted with 573 adolescents with normal weight range in the city of Campinas, Brazil, the prevalence of dissatisfaction with weight was 43.8% (95% CI: 37.9 to 49.8), with greater dissatisfaction found among the girls, adolescents between 15 and 19 years of age, those that had a larger number of appliances in the home, ex-smokers, those that consumed alcoholic beverages and those that reported a medical diagnosis of chronic diseases 26 . In a study conducted in the city of Caruaru (northeast Brazil), 80.8% of adolescent girls and 59.5% of adolescent boys with excess weight (overweight/obesity) wanted to lose weight 27 .…”
Section: Discussionmentioning
confidence: 98%